Evaluating the effects of storage conditions on dry matter loss and nutritional quality of grain legume fodders in West Africa - Akakpo, D.B.; Boer, Imke J.M. de; Adjei-Nsiah, Samuel; Duncan, Alan J.; Giller, Kenneth E.; Oosting, Simon J. (Elsevier, 2020)
Feed scarcity is a major challenge for livestock production in West Africa, especially during the dry season when grass quality and quantity on grazing lands are inadequate. In the dry season, crop residues are a key source of livestock feed. The residues of grain legumes, also known as grain legume fodders (GLFs), are stored and traded for feeding in the dry season. The objectives of our experiment were to evaluate the effects of storage conditions and duration on dry matter (DM) and nutritional quality of GLFs, and to assess the risk of aflatoxin in stored groundnut fodder. The experiment was designed as a factorial trial with 18 treatment combinations with four replicates (4 farms). The treatments included: 3 types of GLFs (cowpea, groundnut and soybean fodder), 3 types of storage locations (rooftop, room and tree-fork) and 2 types of packaging (packed in polythene sacks and unpacked but tied with rope). Over a 120 day storage period, DM quantity reduced by an average of 24 % across all storage conditions, showing a range from 14 % in the best condition (sacks and rooms) to 35 % in the worst condition (bundles tied with rope and stored on rooftops or tree-forks). Soybean fodder had no leaves, the lowest crude protein content (CP) and organic matter digestibility (OMD), and the highest content of cell wall components compared to cowpea and groundnut fodder. These nutritional quality parameters in soybean fodder hardly changed during storage. Cowpea and groundnut fodder showed a decrease in leaf-to-stem ratio (LSR), CP and OMD, and an increase in the content of cell wall components during storage, but their nutritional value remained better than that of soybean fodder. Storage in sacks resulted in less DM loss, in less reduction of LSR and in a smaller increase of the content of cell wall components than storage of bundles tied with rope. Our study shows that the DM loss, the decrease in LSR, and the increase in the content of cell wall components can be prevented partly by storing GLFs in sacks instead of tying bundles with rope, and to a minor extent by storing in rooms instead of in the open air. Aflatoxin was not detectable in the groundnut fodder samples. Our results highlight that attention to storage conditions can improve the feeding value of GLFs which are key for livestock nutrition during the dry season.